Developing Indonesian Language Literacy through Storytelling Activities for Elementary School Students at Pandeglang Regency - Yasser Arafat; Trisna Sonjaya; Marsalino, Marsalino (Sean Institute, 2025)
The problem of Indonesian language literacy skills in elementary school students is: low interest in reading, limited comprehension, and the lack of ability to critically comprehend reading content. Language learning activities tend to focus solely on cognitive aspects, so that students do not get a fun, contextual, and creative learning experience. Storytelling as a form of traditional literacy rich in cultural and linguistic values, has not been optimally utilized in school learning. Therefore, research is needed on the development of Indonesian language literacy through storytelling activities to improve language skills, imagination, and the ability to understand and appreciate texts. This study aims to analyze the effectiveness of storytelling activities in improving Indonesian language literacy skills among elementary school students at Pandeglang Regency. The research method used a descriptive qualitative approach involving classroom teachers, school librarians, and students in grades III–V from several elementary schools. Data were collected through observation, interviews, and document analysis. The results indicate that storytelling activities contribute positively to vocabulary enrichment, improved listening skills, and the ability to understand and re-express story content. Supporting factors include teacher creativity, parental involvement, and the availability of reading materials. However, barriers were also identified, such as limited time, supporting facilities, and a lack of teacher training in storytelling techniques. This study recommends integrating storytelling into structured Indonesian language learning, teacher training, and providing local story sources relevant to the Pandeglang cultural context.